The Association of Depression and Anxiety Disorders With Gastrointestinal Symptoms Among Nurses - Behnam Masihipour; Fariborz Mansour-Ghanaei; Saman Maroufizadeh; Soheil Hassanipour; Mehrnaz Asgharnezhad; Adele Isanazar; Kourosh Mojtahedi; Farahnaz Joukar (Caspian Journal of Neurological Sciences)
Background: The significant overlap of psychological disorders in both functional and organic gastrointestinal (GI) diseases highlights the complex and interconnected relationship between the brain and the gut. Objectives: This study investigated the association between depression and anxiety with GI symptoms among nurses. Materials & Methods: This cross-sectional study was conducted on 460 nurses. All individuals’ clinical characteristics, demographical data and GI symptoms were recorded. Anxiety and depression were assessed using the depression, anxiety and stress scale-21 (DASS-21) questionnaire. Multiple logistic regression analyses were used. Data were analyzed using SPSS software, version 16 and GraphPad Prism software, version 8.0.1, was used to design graphs. Results: The mean age of participants was 30.08±7.43 years and 441 were females. Their mean scores of depression and anxiety were 2.50±4.53 and 4.57±5.59, respectively. The prevalence rates of GI symptoms, depression, and anxiety among nurses were 16.7%, 10.2% and 25.4%, respectively. The frequencies of depression and anxiety were significantly higher among nurses with more work experience (P<0.05). Among those with fixed shifts and upper education, anxiety was more prevalent. The most frequent GI symptom was abdominal pain (5.9%). Depression and anxiety were significantly associated with GI symptoms (P<0.05). A significant association between work experience and the likelihood of experiencing depression (Odds ratio [OR]=3.95, 95% CI: 1.63- 9.57, P=0.002) and anxiety (OR=1.67, 95% CI: 1.02- 2.7, P=0.041) was observed. Conclusion: The study revealed the association between depression and anxiety with GI symptoms among nurses that have been increased by years of working.